Micro-firms way to succeed: How owners manage people - Rodrigues, A. C.; Carvalho, H.; Caetano, António; Santos, S. C. (Journal of Business Research, 2022)
This study explores the configurations of people management practices in micro-firms and their relation with entrepreneurial orientation and firm performance in a four-year window. Based on the ability-, motivation- and opportunity-focused practices framework, we identify configurations of HRM practices used in micro-firms and, in conjugation with entrepreneurial orientation, how they affect employee growth and net income. We analyzed data collected from 114 micro-firm owners combined with firm objective performance measures using Multiple Correspondence Analysis and Cluster Analysis. Results show a taxonomy of three configurations of HRM practices associated with different entrepreneurial orientation strategic postures in micro-firms: “Financial centric HRM practices”, “Operations centric HRM practices”, and “People centric HRM practices”. We assume that configurational methods can help uncover the complexity of the interplay between HRM practices and strategic postures on micro-firm performance. This study contributes to the literature in micro-firms by revealing effective people-related managerial practices on performance.